How can Korea Boost Potential Output to Ensure Continued Income Convergence? - Jain-Chandra, Sonali (IMF Working Papers; Working Paper, 2014)
Korea's rapid growth has slowed in recent years, suggesting lower potential growth. This paper uses an array of techniques, including statistical filters, a multivariate model and the production function, to estimate Korea's potential growth. The main finding is that trend growth has fallen from around 4 3/4 percent during 2000-07 to around 3u -3 1\2 percent by 2011-12. Absent reforms, it is projected to fall further to around 2 percent by 2025, primarily due to declining working-age population. However, Korea's potential growth can be maintained at a higher level by putting in place a comprehensive structural reform agenda, including increased female and youth labor force participation, liberalization of product and labor market regulation. Staff simulations suggest that such reforms could lift potential growth by around 1u percentage point over the next decade, maintaining potential growth at around 3u percent, counteracting the effect of population aging, and enabling Korea to continue to converge to income levels of the United States.